Pelatihan Produksi Video profile Kelompok Wanita Tani Ngudi Makmur Sebagai Media Promosi - Anditha Sari; Ratna Susanti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Abstract. Ngudi Makmur women's farmer group is one of the groups that was established by non-governmental organizations. This farmer group has produced processed products from residents' land. The harvest from this farming is then sold to the surrounding community or from outsiders. As a means of delivering information and promoting processed products, farmer groups need media, one of which is a video profile. The video profileproduction training process is carried out in 3 stages, namely pre-production, production and post-production. In the pre-production process, the authors collect data by means of observation, interviews, documentation and also literature with information related to the object of service activities. The location of the observation in making this video profilewas carried out in the joglo village RW 05. In the production stage, the author used a Canon 1100d DSLR Camera, Canon 1200d DSLR Camera, Canon Fix 50mm STM Lens, Somita Tripod Camera ST-3520 and in the post-production stage in editing using Lenovo thinkped X260 and Adobe Premiere Pro CC 2017. The results from pre- to post-production, the authors together with partners can produce a video profilethat is better able to provide an overview of KWT activities, processed products produced and the achievements of the Women Farmers group.